The Influence of Dowel-Bearing Strength in Designing Timber Pegged Timber Joints. Issue 3 (3rd April 2018) - Ceraldi, Carla; Lippiello, Maria; D'ambra, Claudio; Prota, Andrea
ABSTRACT: The employment of timber pegs in timber structure joints is a widespread technology in the field of timber frame building in the United States, where the Timber Frame Engineering Council has published a special Standard to supplement the National Design Specification for Wood Construction. The authors have been studying the possibility of supplementing the Eurocode 5 design formulas, thought for timber joints with metal connectors, with specifications needed for a reliable design when employing timber pegs. The field of application envisaged is that of restoring timber structures and results obtained until now are quite encouraging. In this step of the research, more attention has been paid to deformation process: fir and chestnut samples have been tested to determine their dowel-bearing behavior with steel and ash timber peg while double-shear plane joints made of the same wood species, and fastened with steel as well as timber pegs, have been analyzed.